Light‐Driven Amphibious Mini Soft Robot Mimicking the Locomotion Gait of Inchworm and Water Strider - Pengfei Zhu; Kedong Shang; Yinpeng Huang; Zhongbao Jiang; Jian Zhou; Xulei Lu; Tingting Yang (Advanced Intelligent Systems, 2024)
Amphibious robots, which are expected to move agilely in both land and water environments with huge differences in medium density, have always been a hot spot in the field of robotics. However, limited by the simple structure and drive system, the existing mini‐robots have a relatively single‐movement mode, which limits their ability to move in complex environments. This article fuses two different biomimetic morphological features to create an amphibious mini‐robot: mimicking the body shape and gait of a terrestrial inchworm, and mimicking the superhydrophobic leg shape and gait of an aquatic water strider. The light‐driven approach also brings the advantage of remote wireless manipulation. The mass of the robot is only 8 mg, and it has fast land movement speed (≈0.05 times body length s−1), water surface movement speed (≈0.5 times body length s−1), and some obstacle‐crossing ability (over obstacles of ≈64% of the robot's height). Moreover, the robot can quickly switch from land to water locomotion, which is expected to facilitate emerging applications in various industrial and biomedical settings.